PROFESI GURU DALAM PERSPEKTIF AL-QURâ€™AN - Wiyono, Ahmad Hadi (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2018)
The teacher profession is now one of the most prestigious jobs. In some universities, one of the majors that is loved by prospective students is the department of teacher training and education.The role of the teacher is so important and decisive. He scored a blue young generation. Therefore, if the teacher does not meet the requirements of ideal quality and quantity, it will result to the intellectual, emotional, social and kinesthetic development of learners.To know the character of the teacher in the perspective of the Quran, can be seen from the terms that are meaningful with the teacher. Therefore it is necessary to make a special study related to the teacher who obtained the source directly from the Quran as a theological foundation in living the profession as a Quran teacher. Keywords: professions, teachers and the Quran